PENINGKATAN KUALITAS LINGKUNGAN MELALUI BANK SAMPAH DAN TANAMAN BUNGA DALAM POT (TABULAMPOT) - Nur Farida; Iqbal Ainur Rahman; Ayu Fitriana; Klarista Miftahul Dwiayunin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Environmental issues, particularly waste accumulation and a lack of green open spaces, are critical issues in densely populated areas such as Jalan Gersikan VI, Pacar Keling, Tambaksari, Surabaya. This community service program through the Community Service Learning (CSL) activity aims to increase residents' awareness and participation in waste management and environmental greening. The implementation of the activities was carried out in several stages: observation, planning, implementation, and evaluation. The program began with a waste bank initiative as a platform for managing economically valuable inorganic waste. Additionally, the cultivation of Potted Flower Plants (TABULAMPOT) was implemented as a greening solution for limited land areas. The results of the activities demonstrated a significant increase in community participation, the volume of waste successfully managed, and improved environmental aesthetics. This program successfully created a sustainable, self-reliant, and economically valuable environmental management model, proving that the synergy between waste banks and greening can be an effective solution to urban environmental issues.